RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS (SIG) OBJEK ARKEOLOGI BERBASIS WEB PADA MUSEUM BLAMBANGAN KABUPATEN BANYUWANGI - Rina Utari; Muhasshanah Muhasshanah; Bayu Ari Wibowo (CV. Denasya Smart Publisher, 2025)
The historical and cultural identity of Banyuwangi Regency needs to preserve its archaeological heritage. Assigning sites of historical value has, over the years, been left undertaken or ignored by the community at large. The advent of a Geographical Information System has provided an avenue for addressing these challenges through site documentation, preservation, and ease of access for navigation. In this scenario, the accuracy of archaeological data recording and ease of access are of paramount concern and are taken care of by the Banyuwangi Regency Tourism Office.